Thromboxane Mobilizes Insect Blood Cells to Infection Foci - Roy, Miltan Chandra; Nam, Kiwoong; Kim, Jaesu; Stanley, David; Kim, Yonggyun (Frontiers in Immunology, 2021)
Innate immune responses are effective for insect survival to defend against entomopathogens including a fungal pathogen, Metarhizium rileyi, infecting a lepidopteran Spodoptera exigua. Especially, the fungal virulence was attenuated by cellular immune responses, in which the conidia were phagocytosed by hemocytes (= insect blood cells) and hyphal growth was inhibited by hemocyte encapsulation. However, the chemokine signal to drive hemocytes to the infection foci was not little understood. The hemocyte behaviors appeared to be guided by Ca2+ signal stimulating cell aggregation to the infection foci. The induction of Ca2+ signal was significantly inhibited by cyclooxygenase (COX) inhibitor. Under the inhibitory condition, an addition of thromboxane A2 or B2 (TXA2 or TXB2) among COX products was the most effective to recover Ca2+ signal and hemocyte aggregation. TXB2 alone induced a microaggregation behavior of hemocytes under in vitro conditions. Indeed, TXB2 titer was significantly increased in the plasma of the infected larvae. The elevated TXB2 level was further supported by the induction of phospholipase A2 (PLA2) activity in the hemocytes and subsequent up-regulation of COX-like peroxinectins (SePOX-F and SePOX-H) in response to the fungal infection. Finally, expression of a thromboxane synthase (Se-TXAS) gene was highly expressed in the hemocytes. RNA interference (RNAi) of Se-TXAS expression inhibited Ca2+ signal and hemocyte aggregation around fungal hyphae, which were rescued by the addition of TXB2. Without any ortholog to mammalian thromboxane receptors, a prostaglandin receptor was essential to mediate TXB2 signal to elevate Ca2+ signal and mediate hemocyte aggregation behavior. Specific inhibitor assays suggest that the downstream signal after binding TXB2 to the receptor follows Ca2+-induced Ca2+ release pathway from endoplasmic reticulum of the hemocytes. These results suggest that hemocyte aggregation induced by the fungal infection is triggered by TXB2 via Ca2+ signal through a PG receptor.